2016
DOI: 10.3389/fmicb.2015.01461
|View full text |Cite
|
Sign up to set email alerts
|

Selective Pressure of Temperature on Competition and Cross-Feeding within Denitrifying and Fermentative Microbial Communities

Abstract: In coastal marine sediments, denitrification and fermentation are important processes in the anaerobic decomposition of organic matter. Microbial communities performing these two processes were enriched from tidal marine sediments in replicated, long term chemostat incubations at 10 and 25°C. Whereas denitrification rates at 25°C were more or less stable over time, at 10°C denitrification activity was unstable and could only be sustained either by repeatedly increasing the amount of carbon substrates provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The weaker temperature effect indicates that other drivers besides temperature are of importance in controlling denitrification rates. This corroborates the findings of Brin et al (2015) and Hanke et al (2015), who both showed that availability of organic carbon is another key determinant controlling denitrification and its response to warming. In our experiment nitrate concentrations were set at 1 mg N l −1 at the start of the denitrification measurements.…”
Section: Denitrificationsupporting
confidence: 91%
See 2 more Smart Citations
“…The weaker temperature effect indicates that other drivers besides temperature are of importance in controlling denitrification rates. This corroborates the findings of Brin et al (2015) and Hanke et al (2015), who both showed that availability of organic carbon is another key determinant controlling denitrification and its response to warming. In our experiment nitrate concentrations were set at 1 mg N l −1 at the start of the denitrification measurements.…”
Section: Denitrificationsupporting
confidence: 91%
“…For example, in enrichment bioreactors which contained communities derived from marine sediments, warming resulted in changed denitrification activity and community shifts, from a community where fermenters and organisms capable of nitrous oxide reduction were the dominant organic matter degraders at 10 degrees, to a system dominated by denitrifying populations, performing the complete denitrification pathway, at 25 degrees (Hanke et al 2015). Thus, Hanke et al (2015) show that temperature effects on denitrification rates are not only controlled by oxygen, but also by organic carbon, driven by changed interactions between fermenting and denitrifying bacteria. Effects of warming may also depend on the successional stage of microbial communities, as was observed in freshwater biofilms , in which young biofilms showed increased denitrification rates with warming, whereas denitrification rates in older biofilms decreased.…”
Section: Denitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…; Hanke et al . ), the survival of the biocontrol agent (Hu et al . ) and the interactive effects within microbiomes (Thomas & Sekhar ).…”
Section: Discussionmentioning
confidence: 99%
“…In a meromictic lake, microbial iron oxidizers and reducers were found concomitant with high rates of iron oxidation but no detectable iron oxides, suggesting rapid reduction (Berg et al ). Evidence of carbon substrate sharing between fermenters and denitrifiers was shown in a mixed culture from marine sediments (Hanke et al ). Also in marine sediments, recycling of nitrite contributed to higher‐than‐expected rates of sulfide oxidation (Rios‐Del Toro and Cervantes ).…”
Section: Cryptic Interactionsmentioning
confidence: 98%